2007
DOI: 10.1371/journal.pone.0001278
|View full text |Cite
|
Sign up to set email alerts
|

A Virosomal Malaria Peptide Vaccine Elicits a Long-Lasting Sporozoite-Inhibitory Antibody Response in a Phase 1a Clinical Trial

Abstract: ObjectivesPeptides delivered on the surface of influenza virosomes have been shown to induce solid humoral immune responses in experimental animals. High titers of peptide-specific antibodies were also induced in a phase 1a clinical trial in volunteers immunized with virosomal formulations of two peptides derived from the circumsporozoite protein (CSP) and the apical membrane antigen 1 (AMA-1) of Plasmodium falciparum. The main objective of this study was to perform a detailed immunological and functional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…The induced antibody responses were long-lived, as measured one year after the third immunization. The immunogenicity results 38,40 (Okitsu et al, submitted) closely followed the animal results presented in this report, validating the mouse and rabbit model for immunogenicity studies of virosomally formulated vaccine candidates.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 79%
“…The induced antibody responses were long-lived, as measured one year after the third immunization. The immunogenicity results 38,40 (Okitsu et al, submitted) closely followed the animal results presented in this report, validating the mouse and rabbit model for immunogenicity studies of virosomally formulated vaccine candidates.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S supporting
confidence: 79%
“…Invasion inhibition correlated positively with migration inhibition, suggesting that anti-UK-39 antibodies interfered with parasite gliding motility, which is based on the same mechanism of redistribution of proteins along the sporozoite surface as host cell invasion [67] . These results confirmed that the UK-39 mimotope closely resembles the natural conformation of the NANP repeats expressed on the sporozoite surface [66] . Increases in anti-UK-39 antibody avidity over the course of immunizations indicated that B-cell memory was formed.…”
Section: Clinical Development Of Virosomal-based Malaria Vaccinesupporting
confidence: 77%
“…IgG preparations from controls immunized with PEV301 or IRIV alone did not interfere with sporozoite migration or invasion. Antibody titers assessed using ELISA correlated closely with in vitro inhibition of sporozoite migration and invasion of hepatocytes [66] . Invasion inhibition correlated positively with migration inhibition, suggesting that anti-UK-39 antibodies interfered with parasite gliding motility, which is based on the same mechanism of redistribution of proteins along the sporozoite surface as host cell invasion [67] .…”
Section: Clinical Development Of Virosomal-based Malaria Vaccinementioning
confidence: 70%
“…Sera collected from volunteers were used to assess ELIS" and IF" titer to the constrained repeat peptide and P. falciparum (NF5 ) sporozoites, respectively. Of the 21 volunteers immunized with PEV302, 19 demonstrated titers ≥10 2 after three immunizations [102] however, a challenge was not conducted as part of this study. " second trial that included CHMI was conducted with these vaccines where the PEV301 and PEV302 epitopes were combined (known as PEV3") and administered together to 12 volunteers [103].…”
Section: Vaccines Containing Csp Repeatsmentioning
confidence: 99%